Bibliometric Review of the Development of Hedging Strategies in Investment - Judijanto, Loso; Rizani, Ahmad; Sudarmanto, Eko; Safitri, Elvina (Eastasouth Institute, 2024)
This study presents a comprehensive bibliometric analysis of research on hedging strategies in investment, examining trends, collaborations, and emerging themes over time. Using data from key academic databases and VOSviewer for visualization, we identified core research areas, key contributors, and influential institutions. The analysis reveals that traditional themes such as financial markets, commerce, and investment remain central to the literature, while newer areas of focus, including cryptocurrencies, energy markets, and responses to global crises like COVID-19, have gained prominence in recent years. The study also highlights the strong collaborative networks between countries and institutions, with the United States, China, and the United Kingdom emerging as key hubs of research activity. Future research is expected to focus on adapting hedging strategies to new financial risks, including those associated with emerging asset classes like cryptocurrencies, and responding to macroeconomic disruptions. This study contributes to the field by offering insights into its intellectual structure and suggesting directions for further exploration.